A Survey on the Relationship between Leadership Style and Strategy of Conflict Management among Top Managers of Urmia Hospitals: 2013 - Farshad Faghisolouk; Ali Valinejadi; Roghaye Ershad sarabi; Pouran Raeissi (Tehran University of Medical Sciences, 2014)
Background: Hospital as core of health and care system requires an effective leadership style and suitable strategy for organizational differences and conflict' solving. Main goal of this study is to survey of relationship between leadership style and strategy of conflict management among chief executive officers of Urmia hospitals. Materials and Methods: This analytical-descriptive cross-sectional study was implemented in Urmia hospitals in 2013. Study population of the research includes thirty top managers in ten hospitals of Urmia. Data gathered through three questionnaires (personal and job characteristic leadership style with method of Fiedler LPC and conflict management). Data analyzed through SPSS software, mainly by Chi 2, Kruskal-Wallis and Spearman's Rho tests. Results: Results showed that Leadership style had significant statistical relationship with average of managers work experience (p=0.040). Also age and strategy of control had significant statistical relationship (p=0.01). Leadership styles and strategies of conflict management weren't significantly with other descriptive variables such as (position, level of education, marriage situation, work experience, managerial studies and second job). Leadership styles and strategy of conflict management weren't significant relationship, finally. Conclusion: Since that the determination of leadership style and methods of dealing with conflict management in hospitals is important, it is recommended that ever done comprehensive research on the effects of other factors such as organizational culture, social culture, character on leadership style and conflict management.